Popular English Songs as Motivational Resources and Instructional Aids for Grammar Education - John Arvin V. De Roxas; Daisy O. Casipit; Mercedita M. Reyes; Lyan Mae Micah V. Dela Cruz; Joan C. Ravago (Qubahan Academic Journal)
Objectives: The study aimed to investigate the efficacy of incorporating popular English songs as motivational tools in English grammar instruction among 44 Grade 7 Junior High School students. It focused on students' performance in modals, prepositions, and WH-questions, assessing changes in their motivation for language learning based on the Affective Filter Hypothesis Theory and John Eric Adair’s seven key dimensions of motivation. Method: A quantitative research approach was employed, utilizing a quasi-experimental single-group pretest-posttest design. Participants included 44 Grade 7 students. The study, grounded in the Affective Filter Hypothesis Theory, used Adair’s seven key dimensions of motivation as a framework. Students were tested on modals, prepositions, and WH-questions before and after integrating popular English songs into instruction. Statistical analysis of pretest and posttest results focused on t-values and significance levels (2-tailed, p<0.05) to evaluate the intervention's effectiveness. Results: The study found statistically significant improvements in students' motivation and performance following the use of popular English songs in grammar instruction, with a t-value of -14.766 (2-tailed, p<0.05). The intervention enhanced student engagement and motivation across all seven key dimensions: energy, commitment, perseverance, skill, focus, enjoyment, and responsibility. Students' test performance on modals, WH-questions, and prepositions significantly improved post-intervention. Conclusion: In conclusion, incorporating popular English songs into grammar instruction significantly boosts student motivation and performance in English language learning. This approach not only enhances the understanding of specific grammatical concepts but also creates a more engaging and motivating classroom environment. The findings suggest that using music as a pedagogical tool can effectively advance English language education, particularly in similar educational contexts.